Impact of Rocky Topography on Settlement Pattern and Housing Development in Idanre, Nigeria - Omole, F.K; Owoeye, J.O (Richtmann Publishing, 2012)
The pattern of development of urban land-use in relation to topography varies from rural to urban. What distinguishes Idanrecommunity from other Yoruba settlements is the rocky topographical nature that surrounds and abounds within the community. In thispaper, the effect of rock outcrops that surround the community and the effects on its development were investigated. The studyemployed both historical and descriptive analysis to gather relevant data about the origin and locational structure of the town. Therewere 3,620 existing buildings in the area according to the building demographic survey carried out. The seven quarters in the town weresub-divided into twenty-two sectors from which 10.0% of the total buildings in all the sectors were picked as sample size forquestionnaire administration. Our findings in the study show both positive and negative impacts that the rocky topography has on thecommunity. The essential aspect of the discoveries were some viable potentials and topographical features of the town which need to beadequately harnessed and made used off for the benefit of the community and the state at large.